Examining Students' Perceptions towards Video-Based and Video-Assisted Active Learning Scenarios in Journalism and Communication Courses - Fani Galatsopoulou; Clio Kenterelidou; Rigas Kotsakis; Maria Matsiola (MDPI AG, 2022)
Audiovisual content is highly employed in modern education curricula. This study aimed to identify students' perceptions regarding the use of video in the courses they attend. Quantitative research was conducted among students of journalism and communication studies. Four courses were used for this study that employ video-based and video-assisted teaching strategies for active learning. Students used videos in different educational settings for flipped learning, blended learning, and autonomous self-paced learning. Their perceptions were examined through an extended form of the Technology Acceptance Model, encompassing more parameters (such as self-efficacy, perceived enjoyment, satisfaction, attitude, and intention of use) to identify causal relationships. In addition, the roles of technical parameters, such as internet connection, audio quality, and video quality, along with the duration of a video, were explored. The findings reveal students' positive attitudes towards videos, and all factors were significantly related to the intention of use. In addition, the technical aspects of the video did not constitute a problem in the educational process, most likely due to contemporary quality in internet connections and audiovisual productions along with playback equipment. The duration of the videos was also not presented as an issue as there are flexible ways to embed videos in the learning process. Overall, videos can be used in multiple active learning scenarios to enhance students' motivation and engagement and provide a joyful, collaborative, and hospitable learning environment. Students are familiar with digital tools and technologies and seem to enjoy audiovisual material in the learning process.